War Kids - Waller, Todd W. (Waller, Todd W., 1999)
The film is a first-hand account of the war that has torn apart Bosnia, told through the eyes of Muslim and Serbian teenagers in and around Sarajevo. The film captures stories of young survivors of the war - and their perspectives on snipers, ethnic cleansing, dating, politics, music, Americans, and the outlook for the fragile former Yugoslavia.